Post neonatal mortality in a tertiary care center at Garhwal Uttarakhand, India: a retrospective study of 10 years - Tiwari, Varun Kumar; Ali, Haroon (International Journal of Contemporary Pediatrics, 2018)
Background: Institutional childhood morbidity, mortality analysis and their trends reflect the local disease occurrence, changes in treatment modalities and quality of treatment available. This study was aimed to evaluate the magnitude of post neonatal mortality and its seasonal pattern at Hemawati Nandan Bahuguna Teaching Base Hospital, Srikot over a period of 10 years. Methods: A retrospective cross-sectional descriptive analysis was done on post neonatal mortality data by Pediatric Department of the Hemawati Nandan Bahuguna Teaching Base Hospital, Srikot from April 2008 to March 2018. Neonates admitted to PICU, referral and LAMA patients were excluded from the study. Data was analyzed using SPSS 16.0. Results: Overall post neonatal mortality of 1.83% was found in the study. Mortality amongst the boys was 119 (54.34 %) and the girls were 100 (45.66 %). Three most common causes of mortality were septicemia (27.40 %) followed by encephalitis (11.41 %) and protein energy malnutrition/underweight (9.58 %). Among the 219 children who died, the number of deaths were recorded in 29days to 1-year age group (n=102, 46. 57%). Mortality of the girls was higher than boys in 10-14year age group. Maximum mortality was seen in the month of June (29, 13.24%) followed by May (23, 10.5%), August (22, 10.04%) and January (20, 9. 13%). The occurrence of mortality with respect to month was found to be significant (p=0.01). Conclusions: This study showed infectious diseases and protein energy malnutrition/ underweight together constituted two-third of mortality in the institution. Strengthening vaccination program, facilities at tertiary care centers and healthy dietary practices in the community can reduce the post neonatal deaths.